Doubters and Dreamers - Gould, Janice, 1949-2019 (Book collections on Project MUSE., 2011)
"The girl is a young Janet Gould, and the poems and narrations that follow constitute a remarkable work of sustained and courageous self-revelation, retracing the precarious emotional terrain of an adolescence shaped by a mother's tough love and a growing consciousness of an ancestral and familial past. One poem and vignette at a time, Doubters and dreamers explores what it means to be a mixed-blood Native American who grew up urban, lesbian, and middle class in the West"--Page 4 of cover.